Report of the Joint Select Committee on Federal Relations (Document (Connecticut. General Assembly. House of Representatives), 1847)
Report of the Joint Select Committee on Federal Relations, submitted to the Connecticut General Assembly during the May session in 1847. The report contained discussions regarding the Mexican-American War, the annexation of Texas and creation of a state, as well as resolutions to have the United States Congress prohibit slavery in Texas.